40.2k views
25 votes
14x - 2x + 3

12x + 3
3 (4x + 1)
4x+ 1
1
-8
3(5x + 9)
3(5x + 9)
= 3(5x + 9)
= 5x + 9
= x+9
=x

User Sosergio
by
5.1k points

2 Answers

7 votes
14x - 2x + 3 = 0

To solve for x move the constant to the other side…
14x - 2x = -3

Since 14x - 2x are the same we can subtract them…
12x = -3

Now we divide 12 by both sides, which looks like this…
12x/12 = -3/13
x = -3/12

Simplify to get…
x = -1/4 [Answer]
User Himmelspiegel
by
5.6k points
6 votes

Answer:

-1/4

Explanation:

14x - 2x + 3 = 0
12x + 3 = 0
12x = -3
12x/12 = -3/12
x = -1/4

User KG Sosa
by
5.8k points